Comparison of Supplemented Brucella Agar and Modified Clostridium difficile Agar for Antimicrobial Susceptibility Testing of Clostridium difficile - Kim, Gye Hyeong (The Korean Society for Laboratory Medicine, 2014)
BACKGROUND: Antimicrobial susceptibility testing (AST) of Clostridium difficile is increasingly important because of the rise in resistant strains. The standard medium for the AST of C. difficile is supplemented Brucella agar (sBA), but we found that the growth of C. difficile on sBA was not optimal. Because active growth is critical for reliable AST, we developed a new, modified C. difficile (mCD) agar. C. difficile grew better on mCD agar than on sBA. METHODS: C. difficile isolates were collected from patients with healthcare-associated diarrhea. sBA medium was prepared according to the CLSI guidelines. Homemade mCD agar containing taurocholate, L-cysteine hydrochloride, and 7% horse blood was used. For 171 C. difficile isolates, we compared the agar dilution AST results from mCD agar with those from sBA. RESULTS: No significant differences were observed in the 50% minimal inhibitory concentration (MIC(50)) and 90% minimal inhibitory concentration (MIC(90)) of clindamycin (CLI), metronidazole (MTZ), moxifloxacin (MXF), piperacillin-tazobactam (PTZ), and rifaximin (RIX), but the values for vancomycin (VAN) were two-fold higher on mCD agar than on sBA. The MICs of CLI, MXF, and RIX were in 100% agreement within two-fold dilutions, but for MTZ, VAN, and PTZ, 13.7%, 0.6%, and 3.1% of the isolates, respectively, were outside the acceptable range. CONCLUSIONS: The MIC ranges, MIC(50) and MIC(90), were acceptable when AST was performed on mCD agar. Thus, mCD agar could be used as a substitute medium for the AST of C. difficile.